Firm Size as a Moderator of Solvency Determinants in Islamic Life Insurance Companies - Firmansyah, Amrie; Priawan, Ragil Pranata (Jurnal Ekonomi Syariah Teori dan Terapan, 2024)
Indonesia's Sharia life insurance industry faces challenges in maintaining the company's solvency level. Factors such as claim expense ratio, fund change ratio, and company size are crucial in determining the sustainability of company solvency. This study aims to analyze the effect of the claim expense ratio and fund change ratio on the solvency level of Sharia life insurance companies, with company size as a moderating variable. Using a quantitative deductive approach, secondary data was collected from annual financial statements of six full-fledged sharia life insurance companies registered with OJK from 2017 to 2023. The results showed that the claim expense ratio does not affect the solvency level, while the fund change ratio has a negative effect. Company size does not moderate the relationship between the claim expense ratio and solvency level but can moderate the relationship by weakening the negative effect of the fund change ratio on the solvency level.